The association between neonatal mortality and ventilator association pneumonia - Mai El-Sayad Abd El-Hamid; Marwa Fekry Hassan; Mohamed Zaeim Hafez; Mohamed E. EL-Refaey; Wael A. Khattab; Khaled Saleh Ali Elhamaky; Ahmed F. Abdel Ghany; Shymaa Sobhy Menshawy Khalifa (Alexandria Journal of Medicine)
Background Ventilator association pneumonia (VAP) is a common healthcare-associated disease that primarily challenges ventilated neonates in neonatal intensive care units (NICU). This study aims to evaluate the association between neonatal mortality and ventilator-associated pneumonia.Methodology A case-control study involving 115 neonates supplied with mechanical ventilation for a duration exceeding two consecutive calendar days using either an endotracheal tube or tracheostomy from October 2022 to March 2024. The study comprised all neonates.Results Among 115 neonates admitted to the NICU, 7 VAP patients were dead (15.56%) compared to 15 non-VAP patients (21.43%). The multivariate logistic regression analysis indicated that the hospital stays, length of total parenteral nutrition (TPN), intubation duration, reintubation, asphyxia, and surfactant taken were the most variables strongly associated with VAP (p < 0.05). Nevertheless, other indicators did not show any significant correlation with VAP (p > 0.05). Birth weight was found to be a strong predictive ability with an area under the ROC curve of 0.782 (95% confidence interval of 0.637–0.890, p < 0.0001). Using a cutoff birth weight of 1.70 kg, there was 84.4% sensitivity and 64% specificity for predicting the onset of ventilator-associated pneumonia with high accuracy.Conclusion VAP is a major cause of illness; it has a high incidence among neonates on MV. The VAP group received prolonged periods of TPN and intubation. Early removal of the endotracheal tube and adequate enteral feeding may reduce the incidence of VAP in intubated babies.